THE ROLE OF INTRAOPERATIVE NEUROPHYSIOLOGIC MONITORING TO ENHANCE SUCCESSFUL ORTHOPEDIC SURGERY - Sananta, Panji; Wijaya, Anindita Eka Pramana; Putera, Marvin Anthony (MNJ (Malang Neurology Journal), 2022)
One of the main advance in orthopaedic surgery domain has a goal to investigates the safest and harmless method in surgical procedures. Less complications means a better outcome of surgery. One of the commonest risks at orthopaedic surgery is central and peripheral nerve injury. The modality of Intraoperative Neurophysiologic Monitoring (IONM) which act to limit the risk of nerve injury during operative procedure through the evaluation of nerve integrity and function enable the surgeon to decrease injury to the nerve associated with orthopaedic surgical procedure in the operating room. This article aims to explain and describe the latest modality of IONM, its basic concept and its function at surgery. The last part of the article discussed about orthopaedic surgical techniques which use IONM. The authors hope that this article will enhance the knowledge of all the readers about IONM. This article was written based on literature study searched at Google Scholar, Medline and PubMed. The references were taken from a relatively up to date study ranging from 2013-2018. The article was selected according to the authors inclusion criteria and six articles was chosen as the references for this review. As a conclusion, IONM has an important role to increase successful rate of surgery through minimizing nerve injury risk during surgical procedure.